High-value lipids accumulation by Pavlova pinguis as a response to nitrogen-induced changes. (March 2022) - Fernandes, Tomásia; Cordeiro, Nereida
Abstract: The challenges of exploring the potential of microalgal strains for biotechnological applications include the optimization of their cell growth and chemical composition. To overcome this, it is essential to understand the mechanisms that lead to the accumulation of desired products within microalgal cells. In this study, a gradient of nitrogen as nitrate ( N O 3 − − N ) concentrations was used for the preparation of P. pinguis growth medium. The algal growth dynamics, pigments, nutrient uptake, and detailed lipid composition across treatments were assessed. Increasing the N O 3 − − N level led to higher lipid content (21%), a higher cell uptake rate (0.20 pg N O 3 − − N cell −1 d −1 ) and more accumulation of chlorophylls, carotenoids, and high-value lipids. Eicosapentaenoic acid, essential fatty acids, phytol and stigmasterol were the key high-value lipids that were positively influenced by higher N O 3 − − N levels. High N O 3 − − N conditions induced an increase of 54% in total sterol content, while low N O 3 − − N conditions resulted in increased proportions of saturated fatty acids (66% more) and decreased proportions of polyunsaturated fatty acids (14% less). The low N O 3 − − N level also led to higher amounts of monoglyceride (1.60 mg g −1 ; 64% more). The analysis of P. pinguis lipids before and after hydrolysis provided an insight into the composition of the esterified lipids across treatments. N O 3 − − N supplementation was revealed to be an effective strategy for enhancing P. pinguis lipid composition, for nutraceutical and pharmaceutical industries (high N O 3 − − N level). A greater understanding of the N O 3 − − N uptake and the use efficiency by P. pinguis was reached, showing its potential for further biotechnological applications. Graphical abstract: Image 1 Highlights: High nitrogen supply is a useful strategy to trigger high-value lipid production. Increased nitrogen supply prompt PUFA and sterol accumulation. Phytol presented a positive correlation with C16:2ω6, C18:3ω3, EPA, and C18:5ω3. C16:0, C14:0, C18:0 and C16:1ω7 were the main esterified fatty acids for P. pinguis . Nutritional indexes varied significantly with the cultivation conditions.